Malaysia : Financial Sector Assessment Program Housing Market-Technical Note. (IMF Staff Country Reports; Country Report, 2014)
This Technical Note on the housing market in Malaysia focuses on price developments in the Malaysian housing market and of its sustainability. Malaysia maintains a one-fourth time series for the housing prices index, tracing back to the 1990s. The second half of 2010 marks a clear change in the evolution of housing prices. The break-down of the structural relation between housing prices and the macroeconomic variables used in the econometric model is suggestive of an important shift in the dynamics of housing prices, and should be further investigated.